Pelatihan Pembuatan Media Promosi Mudah dan Menarik dengan Aplikasi Canva untuk UMKM di Desa Blerong Kabupaten Demak - Mutiarachim, Atika; Tyoso, Jaluanto Sunu Punjul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This community service aims to provide training in media promotion to UMKM perpetrators in Blerong Village Demak district. The smart industry 6.0 era uses many technologies for business, including in promotional activities. Promotion is the introduction of a product to be better known to the public, which can be done offline or online, using interesting media. Choosing the right promotional media has a significant impact on the success of a promotional activity while increasing consumer interest in buying a product. The village of Blerong has many UMKM manufacturers who are not aware of the impact of the promotion on increased product sales. Easy and exciting promotion media creation training is essential. Canva application was chosen as a tool because it is simple, and provides many interesting templates and lots of free ones, making it easy for UMKM designers to create designs according to their needs. The training is conducted with lectures on promotion, the benefits of technology, and the continued practice of making promotional media. As a result of this activity, participants are more aware of the influence of the promotional media on the success of the promotion activities, so that the product is better known to the consumer while providing the experience to the participants so that they can use Canva.